Numerical Analysis of Indoor Air Characteristics and Window Screen Influence on Particulate Matter Dispersion in a Childcare Center Using Computational Fluid Dynamics - Cathleen Ariella Simatupang; Vladimir Strezov; Suwanna Kitpati Boontanon; Prapat Pongkiatkul; Narin Boontanon; Ranjna Jindal (SAGE Publishing, 2024)
Indoor exposure to outdoor pollutants adversely affects health, varying with building dimensions and particularly ventilation that have critical role on their indoor dispersion. This study assesses the impact of outdoor air on indoor air quality in a child care center. Computational fluid dynamics was utilized to analyze the dispersion of particulate matter, with a specific focus on window screens featuring 6 distinct pore sizes ranging from 0.8 mm to 2 mm and 2 different thicknesses of 0.5 mm and 0.1 mm. Results indicate that the presence of a window screen offers significant advantages in controlling particle infiltration compared to scenarios without a screen, as larger particles tend to pass directly through the window within the breathing zone. The scenario without window screens minimizes pressure drop but lacks enhanced particle capture capabilities. However, for effective particle reduction, the window screen with a pore size of 0.8 mm (R0.8T2) and a thickness of 0.5 mm proves to be the most beneficial, achieving the particle filtering efficiency of approximately 54.16%, while the larger window screen with a pore size of 2 mm and a thickness of 1 mm exhibits the lowest efficiency at about 23.85%. Nonetheless, screens with very small sizes are associated with a high-pressure drop, impacting energy efficiency, and overall window performance. Larger pores with smaller thicknesses (0.5 mm) reduced particle count by approximately 45.97%. Therefore, the significance of window screen thickness beyond pore size for particle reduction efficiency is highlighted, emphasizing screens' role in indoor air quality and health protection.